New tumoricidal semisynthetic ether phospholipid, plasmanyl-(N-acyl)ethanolamine (PNAE(s)) and enhancement of its tumoricidal activity by calcium ions - Kára, J; Konovalova, A L; Krasnova, M A; Liebl, V; Bejsovcová, L (Neoplasma, 1993)
Recently we described a novel, nontoxic, natural ether phospholipid with selective antitumor activity, 1-0-alkyl-2-acyl-sn-glycero-3-phospho-(N-acyl)ethanolamine, i.e., plasmanyl-(N-acyl)ethanolamine (PNAE), isolated from ischemic tissue of chick embryo. The chemical structure of PNAE has been confirmed by partial synthesis. The semisynthetic preparation PNAE(s), 1-0-octadecyl-2-oleoyl-sn-glycero-3-phospho-(N-palmitoyl)ethanolamine, exhibited tumoricidal activity against human tumor cells T24 and mouse sarcoma cells Mcll as well as in vivo against murine sarcomas S-180 and Mcll. PNAE(s) selectively destroyed tumor cell membranes as has been demonstrated by scanning electron microscopy. The antitumor activity of PNAE(s) in vitro and in vivo was significantly enhanced by Ca2+ ions. These results may be explained by selective damage of tumor cell membranes by PNAE(s), increasing also the tumor cell membrane permeability for exogenous Ca2+ ions and altering the intracellular calcium homeostasis in tumor cells. By increased concentration of Ca2+ in tumor cell cytosol selective damage and lysis of tumor cells was induced. The combined use of parenteral administration of PNAE(s) and peroral doses of calcium gluconate may provide a new approach to enhancement of antitumor activity of PNAE(s) by Ca2+ in a very selective and nontoxic antitumor therapy.
Keywords: Calcium; Cell Line; protinádorové látky; lékové interakce; Fibrosarcoma; Drug Screening Assays, Antitumor; vápník; fosfatidylethanolaminy; DNA nádorová; Drug Synergism; buněčné dělení; Thymidine; Sarcoma 180; DNA, Neoplasm; synergismus léků; Animals; lidé; Cell Division; Humans; Drug Interactions; zvířata; fibrosarkom; sarkom 180; Phosphatidylethanolamines; myši inbrední C57BL; Sarcoma, Experimental; nádorové buňky kultivované; myši; inbrední kmeny myší; buněčné linie; thymidin; screeningové testy protinádorových léčiv; Mice, Inbred C57BL; Tumor Cells, Cultured; Mice; Mice, Inbred Strains; experimentální sarkom; Antineoplastic Agents